Behavioural and psychological symptoms and signs of dementia in low and middle income countries - Gunten, Armin von (PAJAR - Pan-American Journal of Aging Research, 2014)
The growing number of people suffering from dementia is a major public health issue. Dementia is accompanied more often than not by behavioural ad psychological symptoms and signs (BPSS). This editorial aims at providing a short discussion of the outstanding importance of BPSS in low and middle income countries (LaMIC).